Engineering non-pathogenic bacteria for auto-transporter-driven secretion of functional interferon - May Tfilin Samuel; Irina Rostovsky; Alona Kuzmina; Ran Taube; Neta Sal-Man (Gut Microbes)
In recent years, various strategies have been developed to enable the oral administration of protein-based drugs (biologics) with the aim of overcoming the degradation and inactivation of these drugs that can occur as they traverse the gastrointestinal tract (GIT). In this study, we investigated bacteria as a delivery vehicle for biologics, harnessing their ability to withstand the harsh gastric environment and deliver therapeutic drugs directly to the intestine. Specifically, we explored using the type 5 secretion system (T5SS) to secrete therapeutic cargoes under simulated gut conditions. Our research focused on EspC, a T5SS protein from enteropathogenic Escherichia coli, and its potential to secrete interferon-α (IFNα), a cytokine with immunomodulatory and antiviral properties widely used in the clinic. We demonstrated that EspC can facilitate the secretion of IFNα variant when expressed in nonpathogenic bacteria. Moreover, this EspC-secreted IFN was able to activate the JAK-STAT pathway, upregulate IFN-stimulated genes, and induce a robust antiviral response in cells. Collectively, these findings provide proof of concept supporting the utilization of the EspC protein as a novel delivery platform for protein-based therapeutics.